Evaluating fungal pathogen resistance across the leaf economics spectrum using the generalist fungus Sclerotinia sclerotiorum - Keisuke O. Watanabe; Kaori Kohzuma; Hiroko Kurokawa; Kouki Hikosaka (Scientific Reports)
Abstract Leaf traits vary widely among plant species, correlating with leaf economics and growth-defense trade-offs. However, the relationship between trait variation and pathogen resistance remains unexplored. Here, we introduce a novel experimental approach to quantitatively assess pathogen resistance using the generalist fungus Sclerotinia sclerotiorum. In this system, leaf discs were infected either through the epidermis, evaluating physical and chemical defense, or a cut surface, solely evaluating chemical defense. We investigated pathogen resistance across 24 species ranging from annual herbs to evergreen tree species. Epidermal infection revealed higher pathogen resistance in evergreens compared with annual herb species, strongly correlated with the leaf economics spectrum. The cell wall content per leaf area explaind 61% of the interspecific variations in the pathogen resistance through epidermal infection. Pathogen resistance following cut-surface infection was associated with the accumulation of defensive chemicals, such as tannins and lignins. Our findings demonstrate how investments in physical and chemical defense enhance pathogen resistance, potentially driving evolutionarily shifts in leaf traits.